Electronic-secure Vehicle Authorization Mechanism (e-SVAM). (2016) - Krishnan, Asha; Shyjila, P.A.; Kizhakethottam, Jubilant J.
Abstract: This work deals with the creation of a real-life android application, where all the necessary details of a vehicle (i.e., Registration Certificate, Insurance Policy and vehicle's Pollution Under Control Certificate) are coordinated and stored by the user without much effort. Quick Response Code (QR-Code), a highly effective and fast readable technology is used for scanning various details of a vehicle. Similarly a parallel application for the inspecting authority of a vehicle is also created to verify the credentials of the vehicle. The inspecting authority needs to scan a unique QR-Code (which is provided separately for every vehicle) into the mobile application. The simple UI(User Interface) provided in the application allows the faster recognition of the availability, or the lack of availability, of the important documents pertaining to that particular vehicle. These applications help in saving significant amount of time and resources which are at present spent on this task. In view of the security risks of exposing personal details of users, greater care has also been given for securing the data by using QR-Codes and securing access to those details.